Fluorinated graphenes as advanced biosensors - effect of fluorine coverage on electron transfer properties and adsorption of biomolecules - Urbanová, Veronika; Karlický, František; Matěj, Adam; Šembera, Filip; Janoušek, Zbyněk; Perman, Jason A; Ranc, Václav; Čépe, Klára; Michl, Josef; Otyepka, Michal; Zbořil, Radek (Nanoscale, 2016)
Graphene derivatives are promising materials for the electrochemical sensing of diverse biomolecules and development of new biosensors owing to their improved electron transfer kinetics compared to pristine graphene. Here, we report complex electrochemical behavior and electrocatalytic performance of variously fluorinated graphene derivatives prepared by reaction of graphene with a nitrogen-fluorine mixture at 2 bars pressure. The fluorine content was simply controlled by varying the reaction time and temperature. The studies revealed that electron transfer kinetics and electrocatalytic activity of CFx strongly depend on the degree of fluorination. The versatility of fluorinated graphene as a biosensor platform was demonstrated by cyclic voltammetry for different biomolecules essential in physiological processes, i.e. NADH, ascorbic acid and dopamine. Importantly, the highest electrochemical performance, even higher than pristine graphene, was obtained for fluorinated graphene with the lowest fluorine content (CF0.084) due to its high conductivity and enhanced adsorption properties combining π-π stacking interaction with graphene regions with hydrogen-bonding interaction with fluorine atoms.
Keywords: Electrons; Fluorine; Adsorption; grafit; adsorpce; elektrony; biosenzitivní techniky; fluor; Biosensing Techniques; Graphite